The effects of tualang honey on female reproductive organs, tibia bone and hormonal profile in ovariectomised rats - animal model for menopause - Sirajudeen Kuttulebbai NM; Sulaiman Siti A; Zaid Siti SM; Othman Nor H (BMC, 2010)
Abstract Background Honey is a highly nutritional natural product that has been widely used in folk medicine for a number of therapeutic purposes. We evaluated whether Malaysian Tualang honey (AgroMas, Malaysia) was effective in reducing menopausal syndrome in ovariectomised female rats; an animal model for menopause. Methods The rats were divided into two control groups and three test groups. The control groups were sham-operated (SH) and ovariectomised (OVX) rats. The SH and OVX control rats were fed on 0.5 ml of distill water. The rats in the test groups were fed with low dose 0.2 g/kg (THL), medium dose, 1.0 g/kg (THM) and high dose 2.0 g/kg (THH) of Tualang honey in 0.5 ml of distill water. The administration was given by oral gavage once daily for 2 weeks. The reproductive organs (uterus and vagina), tibia bone and aorta were taken for histopathological examination while serum for hormonal assays. Results Administration of Tualang honey for 2 weeks to ovariectomised rats significantly increased the weight of the uterus and the thickness of vaginal epithelium, restored the morphology of the tibia bones and reduced the body weight compared to rats in the ovariectomised group. The levels of estradiol and progesterone, in honey treated groups were markedly lower than that in the OVX group. At low doses (0.2 g/kg; THL group) of Tualang honey there was an increased in serum free testosterone levels compared to OVX group (P < 0.01). Progesterone concentrations was significantly decreased in the OVX group as compared to SHAM group (P < 0.05). Conclusions Tualang honey was shown to have beneficial effects on menopausal (ovariectomised) rats by preventing uterine atrophy, increased bone density and suppression of increased body weight. Honey could be an alternative to HRT.